Proposal for improvement in the chocolate production process of the Sol Norteño company, based on the lean manufacturing management model - Quevedo Olaya, Jhonsson Luis (2024)
The purpose of this research was to propose a management model based on Continuous Improvement to optimize the efficiency and productivity of Sol Norteño, a company specialized in the production of cup chocolates. During the analysis, an unsatisfied demand was identified due to instability in process efficiency and product quality, which affected competitiveness and demand in the current market. The proposal for improvement through Lean Manufacturing includes multiple suggestions to reduce time waste, improve quality control and optimize operations through one of its tools, the 5S.